VIM-AS1, which is regulated by CpG methylation, cooperates with IGF2BP1 to inhibit tumor aggressiveness via EPHA3 degradation in hepatocellular carcinoma - Su-hyang Han; Je Yeong Ko; Sungju Jung; Sumin Oh; Do Yeon Kim; Eunseo Kang; Myung Sup Kim; Kyung-Hee Chun; Kyung Hyun Yoo; Jong Hoon Park (Experimental and Molecular Medicine)
Abstract Early tumor recurrence in hepatocellular carcinoma (HCC) remains a challenging area, as the mechanisms involved are not fully understood. While microvascular invasion is linked to early recurrence, established biomarkers for diagnosis and prognostication are lacking. In this study, our objective was to identify DNA methylation sites that can predict the outcomes of liver cancer patients and elucidate the molecular mechanisms driving HCC aggressiveness. Using DNA methylome data from HCC patient samples from the CGRC and TCGA databases, we pinpointed hypermethylated CpG sites in HCC. Our analysis revealed that cg02746869 acts as a crucial regulatory site for VIM-AS1 (vimentin antisense RNA1), a 1.8 kb long noncoding RNA. RNA sequencing of HCC cells with manipulated VIM-AS1 expression revealed EPHA3 as a pathogenic target of VIM-AS1, which performs an oncogenic function in HCC. Hypermethylation-induced suppression of VIM-AS1 significantly impacted HCC cell dynamics, particularly impairing motility and invasiveness. Mechanistically, reduced VIM-AS1 expression stabilized EPHA3 mRNA by enhancing the binding of IGF2BP1 to EPHA3 mRNA, leading to increased expression of EPHA3 mRNA and the promotion of HCC progression. In vivo experiments further confirmed that the VIM-AS1‒EPHA3 axis controlled tumor growth and the tumor microenvironment in HCC. These findings suggest that the downregulation of VIM-AS1 due to hypermethylation at cg02746869 increased EPHA3 mRNA expression via a m6A-dependent mechanism to increase HCC aggressiveness.